2021
DOI: 10.3390/app11041617
|View full text |Cite
|
Sign up to set email alerts
|

Mining Pool Selection under Block WithHolding Attack

Abstract: In current Proof-of-Work (PoW) blockchain systems, miners usually form mining pools to compete with other pools/miners in the mining competition. Forming pools can give miners steady revenues but will introduce two critical issues. One is mining pool selection, where miners select the pools to join in order to maximize their revenues. The other is a Block WithHolding (BWH) attack, where pools can inject part of their hash/mining power into other pools to obtain additional revenues without contributing to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Answer: Most current research on the game theory of mining pools facing BWH attacks uses static game methods to model two mining pools [36][37][38][39]. There are expected to be very few studies on the dynamic game of the two mining pools because when the two mining pools are modeled, there are only four situations in which the mining pool launches BWH attacks that are easy to model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Answer: Most current research on the game theory of mining pools facing BWH attacks uses static game methods to model two mining pools [36][37][38][39]. There are expected to be very few studies on the dynamic game of the two mining pools because when the two mining pools are modeled, there are only four situations in which the mining pool launches BWH attacks that are easy to model.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous kinds of research focus on analyzing and addressing how miners choose mining pools to obtain optimal profits when facing BWH attacks. Fujita et al [37] applied reinforcement learning (RL) techniques to analyze the optimal pool selection of miners. This work effectively addressed the issue of the mining pool's strategy to attract more miners to obtain the optimal block reward when the two mining pools face a BWH attack.…”
Section: Research Progress and Related Workmentioning
confidence: 99%
“…Reference [30] established a game model between mining pools based on the PoW consensus algorithm, and found that the mining pool can increase its infiltration rate and average income by increasing the mining pool power and the betrayal rate of miners. Reference [31] built a game model of mutual attacks between mining pools and study the impact of different block withholding (BWH) attack intensity on miners' income. It is found that only when the BWH attack intensity is lower than a certain threshold, it can lead to an improvement of miners' income in the mining pool, so as to attract more miners to join the mining pool.…”
Section: Introductionmentioning
confidence: 99%